METODE ITERASI OPTIMAL BERORDE EMPAT UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Yanti, Helmi Putri; M., Imran; Pane, Rolan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article, we discuss the derivation of an optimal iterative method using a quadratic polynomial, which is a review and a correction of a part of Fern´andez-Torres and V´asquez-Aquino’s article [Advances in Numerical Analysis, 10: 1-8, 2013]. Analytically we show that the obtained method has an order of convergencefour and requires three function evaluations per iteration, so that the efficiency index of the method is 1.587. The analytical results are in agreement with the com-putational examples. Numerical comparisons show that the method obtained can compete with the existing fourth order methods.